Persepsi Masyarakat Kenagarian Sumani Tentang Kesiapsiagaan Bencana Gempa Bumi - Helfi Agustin (Jurnal Kesehatan Komunitas, 2014)
Sumani district had the worst impact by earthquake in West Sumatra in 2007. According to a geologists, Sumani is Sumateran faults area which passes along by the mountain of Bukit Barisan start from the Gulf Semangko up to Banda Aceh. The purpose of this study was to illustrate perception of the society of Sumani district about disaster preparedness, because the myths and misperceptions related to natural disasters often give unfavorable impact in disaster management. This is a descriptive research. The population are amount 1376. Sample are 100 people who has experienced in earthquake situation in 2007 and 2009. Technique sampling by using proportionale random sampling from 12 area in Sumani district. The results of the study, 65% of peoples still have the conventional paradigm about the disaster, 80% of peoples believe that they can participate in disaster risk reduction, 68% of peoples thought they need international medical assistance, 43% of peoples believe they are able to take responsibility for their own survival after the earthquake. Disaster education should be done by continually, so the peoples alert to the threat and they has ability to prevent, anticipate, dodge and re-bounce after disaster